1998
DOI: 10.1093/arclin/13.5.433
|View full text |Cite
|
Sign up to set email alerts
|

Motivation for Traumatic Brain Injury Rehabilitation Questionnaire (MOT-Q): Reliability, Factor Analysis, and Relationship to MMPI-2 Variables

Abstract: A Likert scale questionnaire was developed to assess motivation for postacute rehabilitation by traumatic brain injury patients. Items were designed to reflect head-injured individuals' statements about their attitudes toward head injury rehabilitation. Factors such as denial of illness, anger, compliance with treatment, and medical information seeking behavior were used to assess unfavorable and favorable components of motivation. Reliability was assessed using Cronbach's Alpha, which was found to be 0.91 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 0 publications
2
46
0
Order By: Relevance
“…Thus, it was originally validated against the MMPI, which is a measure of psychopathology (Caldwell, 1988). Chervinsky et al (1998) administered it to 174 patients with TBI who were a mean of 6 months post-injury. The total possible score on the MOT-Q is 62 and the mean total score on Chervinsky et al's population was 17.4 (SD ¼ 20.6).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it was originally validated against the MMPI, which is a measure of psychopathology (Caldwell, 1988). Chervinsky et al (1998) administered it to 174 patients with TBI who were a mean of 6 months post-injury. The total possible score on the MOT-Q is 62 and the mean total score on Chervinsky et al's population was 17.4 (SD ¼ 20.6).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, as previous studies have highlighted the importance of adjustment factors, the MOT-Q (Chervinsky et al, 1998) will be added to the model in order to explore whether such factors add any predictive value.…”
Section: The Theory Of Planned Behaviour (Tpb)mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, and most importantly, future studies might investigate the impact of belief schemata on motivation and engagement in rehabilitation, perhaps employing measures similar to those in studies by Schönberger et al (2006a), Bains et al (2007), or Chervinsky et al (1998). The impact on psychosocial outcome should also be explored in line with longitudinal studies in other health conditions that have demonstrated the influence of illness beliefs on a range of functional outcomes (e.g., Groarke, Curtis, Coughlan, & Gsel, 2005;Searle, Norman, Thompson, & Vedhara, 2007).…”
Section: Study Limitationsmentioning
confidence: 99%
“…Motivational problems such as denial, irritability, apathy, and unawareness (Chervinsky et al, 1998) are often linked to reduced responsiveness to reward or to a difficulty producing goal-directed behaviors. Self-awareness has been correlated with severity of injury based on the GCS upon admission (Prigatano et al, 1998).…”
Section: Research Findings Pertaining To Executive Functions In Modermentioning
confidence: 99%